Interaction of Cetrimide with Nonionic Surfactants—Triton X-100 and Brij-35: A Conductometric and Tensiometric Study - Ali, A.; Malik, N.A.; Farooq, U.; Tasneem, S.; Nabi, F. (Springer Verlag (Germany), 2016)
Conductometric and surface tension techniques were employed to study the different mole fractions of nonionic surfactants (TX-100 and Brij-35) with cetrimide. The standard Gibbs energies of micellization ((Formula presented.)) and the Gibbs energies of transfer ((Formula presented.)) in the mixture of surfactants were also calculated; the micellization becomes more spontaneous on increasing the amount of nonionic surfactants in the mixture. It was observed that the values of excess surface concentration (Γmax) in surfactant mixtures decrease in comparison to the pure surfactants but the values of minimum area per surfactant molecule (Amin) increase in surfactant mixtures than in the pure ones. It was also observed that the values of the interaction parameter (β) are negative at all mole fractions. A gradual decrease in β with temperature is observed indicating the synergism between the two components and is attributed to the decrease in the electrostatic repulsion between the charged heads of the cationic surfactant as the nonionic surfactant is being intercalated into the micelle. The activity coefficients were found out to be less than unity confirming nonideality of the system and the negative values of excess free energy of mixing confirm that the mixed micelles formed were stable.